DAMPAK PERUBAHAN PENGGUNAAN LAHAN SEPANJANG PANTAI UJONG BLANG LHOKSEUMAWE TERHADAP PEMUNDURAN GARIS PANTAI - Ishaq Rizal (EKOTON, 2012)
Tourism development of Ujong Blang Lhokseumawe beach gives negative impact to physical beach, such as abration and the changes of shore-area and shoreline. The samples of this study were assigned by purposive sampling. The data were analysed by using comparative method and overlay map of the land-use area of Ujong Blang beach. The result shows the tourism development of Ujong Blang Lhokseumawe beach gives negative impact on the shift of shore-area functions as protection area to economic activity area. The consequency of the changes is the fasten of abration process that was marked by the decreasing of shore-line, in which the shore-line more closer to landward area than before.